(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The problem of management, national economy and public education, healthcare, development of culture and sports, development of small and medium-sized businesses is one of the important issues affecting the fate of our entire people. At the same time, the search for effective methods of leadership and the establishment of a management system are among the priority areas of our country’s development. Because this is how progress has been achieved in the most developed countries of the world. Therefore, if leadership activities in our society are properly organized, there is no doubt that many problems facing our country and our people will find their solutions, our country will be prosperous, and our lives will be comfortable. But frankly, it is clear that leadership activities in our society and their effectiveness are not up to the required level.